Chlorine isotopes constrain a major drawdown of the Mediterranean Sea during the Messinian Salinity Crisis - G. Aloisi; J. Moneron; L. Guibourdenche; A. Camerlenghi; I. Gavrieli; G. Bardoux; P. Agrinier; R. Ebner; Z. Gvirtzman (Nature Communications)
Abstract Hydrological restriction from the Atlantic Ocean transformed the Mediterranean Sea into a giant saline basin during the Messinian Salinity Crisis (5.97–5.33 million years ago). It is still unclear if the deposition of nearly one million km3 of evaporite salts during this event was triggered by a major (≥1 km) evaporative drawdown, or if it took place in a brine-filled Mediterranean connected to the Atlantic. Here we present evidence for a two-phase accumulation of the Mediterranean salt layer based on the chlorine stable isotope composition of halite. During the first phase, lasting approximately 35 kyr, halite deposition occurred only in the eastern Mediterranean, triggered by the restriction of Mediterranean outflow to the Atlantic, in an otherwise brine-filled Mediterranean basin. During the second phase, halite accumulation occurred across the entire Mediterranean, driven by a rapid (<10 kyr) evaporative drawdown event during which sea-level dropped 1.7–2.1 km and ~ 0.85 km in the eastern and western Mediterranean, respectively. During this extreme drawdown event, the eastern Mediterranean basin lost up to 83% of its water volume, and large parts of its margins were desiccated, while its deep Ionian and Herodotus sub-basins remained filled with >1 km-deep brine.